Synthesis, anticancer activity, toxicity evaluation and molecular docking studies of novel phenylaminopyrimidine-(thio)urea hybrids as potential kinase inhibitors - TÜRE, ASLI; KÜÇÜKGÜZEL, İLKAY (ELSEVIER SCI LTD, 2019)
Thirty-two novel urea/thiourea compounds as potential kinase inhibitor were designed, synthesized and evaluated for their cytotoxic activity on breast (MCF7), colon (HCT116) and liver (Huh7) cancer cell lines. Compounds 10, 19 and 30 possessing anticancer activity with IC50 values of 0.9, 0.8 and 1.6 mu M respectively on Huh7 cells were selected for further studies. These hit compounds were tested against liver carcinoma panel. Real time cell electronic sensing assay was used to evaluate the effects of the compounds 10, 19 and 30 on the growth pattern of liver cancer cells. Apoptotic cell death and cell cycle analysis upon treatment of liver carcinoma cells with hit compounds were determined. A significant apoptotic cell death was detected upon treatment of Huh7 and Mahlavu cells with compound 30 after 48 h of treatment. Additionally, compound 10 caused cell cycle arrest at G0/G1 phase. Mutagenicity of hit compounds was evaluated. Assertively, these compounds were not found to be mutagenic on Salmonella typhimurium strains TA98 and TA100. To understand the binding modes of the synthesized compounds, molecular docking studies were performed using the crystal data of VEGFR and Src-kinase enzymes in correlation with anticancer activities.
Keywords: Phenylaminopyrimidines; Ureas; Thioureas; Cancer; Molecular docking; Src-kinase; VEGFR; BIOLOGICAL EVALUATION; THIOUREA DERIVATIVES; UREA DERIVATIVES; DESIGN; IMATINIB